Effect of different diets on proteolytic enzyme activity, trypsinogen gene expression and dietary carbon assimilation in Senegalese sole (Solea senegalensis) larvae - Gamboa Delgado, Julián; Le Vay, Lewis; Fernández Díaz, Catalina; Cañavate, José Pedro; Ponce, Marian; Zerolo, Ricardo; Manchado, Manuel (2011)
The effect of diet on larval growth, anionic trypsinogen gene expression (ssetryp1), and trypsin and chymotrypsin activities was assessed in Solea senegalensis. Changes in larval carbon stable isotope (δ13C) composition were used to estimate carbon assimilation. Diets were supplied for 20 d to fish held in larval rearing tanks and consisted of live rotifers, Artemia nauplii, rotifers followed by Artemia, rotifers co-fed with inert diet and inert diet alone. Growth was significantly faster in larvae fed only Artemia and those fed rotifers and Artemia (k= 0.381-0.387 d-1). Trypsin and chymotrypsin activities increased from 3-4 days after hatching (DAH) in all dietary treatments, while ssetryp1 transcripts increased at 4-5 DAH only in larvae fed live prey. ssetryp1 gene expression was activated later in larvae fed only Artemia and this corresponded with Artemia δ13C values being reflected in larval tissue. Larval δ13C values also indicated greater selection and/or assimilation of rotifers in relation to the inert diet. Results demonstrate that during early larval development of sole, diet modulates ssetryp1 gene expression. The rapid and intense response to diets that promoted different growth and survival suggests the suitability of this biomarker as a nutritional status indicator in early sole larvae.